Chronic anemia and non-ST elevation acute coronary syndrome – double jeopardy. (1st September 2016) - Freeman, Phillip; Berrill, James; Green, John; Anderson, Richard
Abstract: This review outlines the priorities from cardiology and gastroenterology perspectives, resolves some of the misconceptions, and uses the evidence available to suggest strategies for optimizing management of these patients. The dual presentation of acute active gastrointestinal (GI) blood loss together with an acute coronary syndrome (NSTEACS or STEMI) is outside the remit of this review but has been previously reviewed by our group. The review covers NSTEACS together with chronic or sub-acute anemia, anemia that cannot be accounted for by chronic kidney disease, heart failure, or inflammatory disorders. Identification of a potential GI etiology of anemia is important as it allows adjustment to both GI and CV investigations and treatments that can reduce the likelihood and impact of bleeding complications.